2016
DOI: 10.1097/mpg.0000000000001138
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Endothelial Dysfunction With Adhesion Molecules in Patients With Celiac Disease

Abstract: These results show that serum adhesion molecule levels are higher in patients with CD. Some of the risks associated with endothelial dysfunction may be related to CD and these risks can be reduced with an appropriate and fully controlled diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Adhesion molecules like ICAM-1, VCAM-1, and E-selectin are expressed on the membrane surface of endothelial cells and mediate adhesion of various leukocyte types, such as lymphocytes and monocytes, to the vascular endothelium 40 , 41 . Therefore, high levels of adhesion molecules have been considered to be an early indicator of endothelial dysfunction 42 . In the present study, HG obviously increased the expression of these three molecules ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion molecules like ICAM-1, VCAM-1, and E-selectin are expressed on the membrane surface of endothelial cells and mediate adhesion of various leukocyte types, such as lymphocytes and monocytes, to the vascular endothelium 40 , 41 . Therefore, high levels of adhesion molecules have been considered to be an early indicator of endothelial dysfunction 42 . In the present study, HG obviously increased the expression of these three molecules ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The present evidence of altered endothelial function is in line with clinical studies that showed impaired flow-mediated dilation in CeD patients compared to healthy controls [ 34 ]. In this vein, other studies showed elevated levels of soluble vascular adhesion molecule-1, soluble intercellular adhesion molecule-1 and soluble endothelial selectin [ 35 ] and plasmatic oxidative stress [ 36 ] in CeD subjects.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, the coagulopathy or thrombotic condition that can be seen in celiac disease is attributed to causes such as chronic inflammation, endothelial damage, the presence of phospholipid Ig A autoantibodies, and hyperhomocysteinemia due to protein loss in the intestinal wall or related to folate deficiency. [19][20][21] In children, while thrombocytopenia and coagulopathy are rarely seen in the course of celiac disease, this association has been described for the first time in the celiac crisis. This case highlights that a celiac patient may present with a severe illness like sepsis and may be associated with thrombocytopenia and coagulopathy in the crisis.…”
Section: Case Reportmentioning
confidence: 98%